Behold the Buddha: religious meanings of Japanese Buddhist icons - Dobbins, James C. (University of Hawaiʻi Press, 2020)
Attraction and aversion to Buddhist icons -- The Buddhist image as sacred story -- The expressive detail: Buddhist symbolism and iconography -- Fully enlightened Buddhas -- Miraculous Bodhisattvas -- Other mythic Buddhist figures -- Buddhist icons as living entities -- Beyond the Buddha image.